Ting zhi nei hao : guo yi ge bu lei de ren sheng - Ruo, Shan. (Nanjing : Jiangsu Phoenix Literature and Art Publishing House, 2022)
The author of this book describes the manifestations of "self-internal attrition" from the aspects of his own experience and counseling examples, and puts forward some practical methods to help readers get out of their psychological dilemmas, and strive to help young people get rid of the psychological state of internal attrition.
Keywords: Procrastination; Decision making; Self-actualization (Psychology)